Preparation and evaluation of "sustained-action" isoniazid tablets - Muzaffar, Naim Anwar 1935-
The first oral sustained action oral dosage form was introduced in 1952. It consisted of small spherical pellets filled into hard gelatin capsules. The preparation of sustained action dosage forms was further investigated and various methods of preparation and evaluation were described. The use of fatty acids, alcohols and esters and the combination of glyceryl monostearate and beeswax as coating materials for the granules were tried. The present study was focused to prepare and evaluate the sustained action tablets of isonicotinic acid hydrazine. The drug was selected due to its wide use in the treatment of tuberculosis and its properties which facilitate its preparation in sustained action form. Different methods of preparation using different binders and different number of coats were tried. Each batch of prepared tablets was subjected to in vitro evaluation and the results, tabulated and plotted to assess the availability of the drug from the tablets during the nine hours period. The assaying operation was performed after each hour to find the amount of isonicotinic acid hydrazine released. Formulation D after evaluation was found to be most satisfactory, so another confirmatory evaluation test was performed.